2016
DOI: 10.1080/13607863.2016.1199013
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and psychological symptoms of dementia in older residents in long-term care facilities in Japan: a cross-sectional study

Abstract: The prevalence of BPSD in LTC facilities was relatively low compared with other countries. The factors found to relate to BPSD may provide useful information for developing care methods to address BPSD in LTC residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
(60 reference statements)
3
11
2
2
Order By: Relevance
“…In addition, it was observed that the type and degree of sexual or intimate interaction influences the attitudes of nursing professionals working in the Nursing Home. These data corroborate a survey conducted in Japan, which revealed that team members generally show greater acceptance of behaviors perceived as affectionate and respond to eroticism with anger and objection, usually responding to behaviors in ways that range from humor to direct censorship (6) .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, it was observed that the type and degree of sexual or intimate interaction influences the attitudes of nursing professionals working in the Nursing Home. These data corroborate a survey conducted in Japan, which revealed that team members generally show greater acceptance of behaviors perceived as affectionate and respond to eroticism with anger and objection, usually responding to behaviors in ways that range from humor to direct censorship (6) .…”
Section: Discussionsupporting
confidence: 85%
“…Nursing Home for the Elderly are seen as spaces which generally deprive previous projects including family, home and relationships built in the previous phase of life history of the elderly (5) . Their routine is often limited to performing the same activities with the same group of people at the same time, and in this sense meeting the institutional and not the personal requirements (6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Japan's LTC system was established in 2000 to support older people with LTC demands and alleviate the burden of caregiving on family members [40]. People choosing to use LTC services, including in-home, facility, and community services, reduce their financial expenses and improve their quality of care [41]. Taiwan established LTCA 1.0 in 1998, and amended it to develop LTCA 2.0 in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…선행연구에 의하면 치매 노인의 정신행동 증상에 영향을 주는 요 인은 주로 치매 노인의 성별 [14]과 인지 [3,15,16], 통증 [8], 우울 [16], 일상생활 수행능력 [4], 간호제공자의 우울과 치매에 대한 지식 [13] 등이었다. 또한, 환경 요인으로는 소음과 요양실의 형태 [17,18] ADL=activities of daily living; dBA=decibel with A-weighting; yr=year.…”
unclassified